A method for producing a titanium-based inert anode

CN116905058BActive Publication Date: 2026-10-09CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310682498.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2026-10-09
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

然而从使用效果来看,这种方式只能在一定程度上缓解表面活性层脱落的问题,但也增大了表面功能层与基体金属之间的电子传递电阻

Benefits of technology

[0027] This invention proposes a method for preparing a titanium-based inert anode, which mainly involves electrodepositing two metal coatings on a titanium substrate, oxidizing the second metal coating in situ to serve as the intermediate layer of the inert anode, and finally coating an active manganese dioxide layer on the electrode surface with the intermediate oxide layer to obtain a titanium-based inert anode with good electronic conductivity and electrocatalytic activity, and good bonding between the functional layer, the intermediate layer and the metal substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116905058B_ABST
    Figure CN116905058B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a titanium-based inert anode. A first metal plating layer is first electrodeposited on the surface of a titanium base to obtain an electrode A containing the first metal plating layer, a second metal plating layer is second electrodeposited on the surface of the electrode A to obtain an electrode B containing the double metal plating layer, the electrode B is soaked in an acidified oxidant solution to obtain an electrode C with a metal oxide layer after reaction, and a manganese dioxide layer is arranged on the surface of the electrode C to obtain the titanium-based inert anode. The titanium-based inert anode can be used as an inert anode in an acidic medium, and has the advantages of low oxygen evolution overpotential and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical technology, and specifically to a method for preparing a titanium-based inert anode. Background Technology

[0002] In metal electrodeposition and other electrochemical industries, the development and adoption of lead-free anodes to replace lead-based anodes is a general trend in order to reduce energy consumption and lead content in electrodeposited products to meet environmental protection requirements. Among lead-free anodes, titanium-based stable anodes (DSA) are currently the most studied type of electrode. This electrode is mainly made of titanium plate as substrate, coated with a coating containing platinum group metal oxides and TiO2 and other active components, and then cured at high temperature. Because the active components such as RuO2 on the electrode surface have unique electronic conductivity and electrocatalytic activity, they have a significant electrocatalytic effect on the evolution of oxygen in the anode, which can significantly reduce the oxygen evolution potential, thereby reducing the cell voltage in processes such as metal electrodeposition. However, this type of electrode has high manufacturing costs due to the need to coat the surface with noble metal oxides, and its service life cannot fully meet the requirements of hydrometallurgy.

[0003] To reduce the fabrication cost of this type of anode, numerous studies have been conducted both domestically and internationally in recent years on the fabrication of functional layers on titanium substrates using base metal oxides instead of noble metal oxides. Among base metal oxides, MnO2, SnO2, and PbO2 exhibit good corrosion resistance and electrocatalytic activity, and are widely used as active or intermediate layers in anode materials. However, most studies still employ a brush-coating-thermal-decomposition process when fabricating these oxide electrodes, whether for intermediate or surface active layers. In these electrodes, due to the difference in lattice structure and thermal expansion coefficient between the oxide and the titanium substrate, numerous cracks develop on the MnO2 surface of the titanium during processing and use, leading to coating detachment and passivation of the titanium substrate.

[0004] To address this issue, the current main method is to brush an intermediate oxide layer between the titanium metal substrate and MnO2. However, in terms of effectiveness, this method can only alleviate the problem of surface active layer detachment to a certain extent, but it also increases the electron transfer resistance between the surface functional layer and the substrate metal. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing a titanium-based inert anode with a long service life and high catalytic activity.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] The present invention discloses a method for preparing a titanium-based inert anode, wherein a first metal coating is deposited on the surface of a titanium substrate to obtain an electrode A containing the first metal coating, and a second metal coating is deposited on the surface of electrode A to obtain an electrode B with a bimetallic coating. Electrode B is immersed in an acidified oxidant solution and reacted to obtain an electrode C with a metal oxide layer. A manganese dioxide layer is then deposited on the surface of electrode C to obtain a titanium-based inert anode.

[0008] The preparation method of the present invention involves sequentially electrodepositing two metal coatings on a titanium substrate, and then oxidizing the second metal coating in situ to serve as the intermediate layer of the inert anode. Finally, an active manganese dioxide layer is coated on the electrode surface with the intermediate oxide layer to obtain a titanium-based inert anode with good electronic conductivity and electrocatalytic activity, and with good bonding between the functional layer, the intermediate layer and the metal substrate.

[0009] In a preferred embodiment, the titanium substrate is first subjected to surface acid treatment in an acid solution.

[0010] A roughened titanium substrate is obtained by surface acid treatment of the titanium substrate in an acid solution, which increases the adhesion between the subsequent coating and the titanium substrate.

[0011] Further preferably, the acid solution is one or more selected from dihydroxytartaric acid, maleic acid, dimethyloxaloacetic acid, dihydroxymaleic acid, oxalic acid, dichloroacetic acid, dinitrobenzoic acid, 2-ethylmalonic acid, and 2,6-dihydroxybenzoic acid; in the acid solution, H + The concentration is 0.1–1 mol / L, preferably 0.1–0.50 mol / L.

[0012] In a preferred embodiment, the metal in the first metal plating layer is selected from at least one of nickel, cobalt, and copper, and includes nickel, wherein the mass fraction of nickel in the first metal plating layer is 70-100%, preferably 80-90%.

[0013] The first metal coating contains nickel, and the nickel content is required to be greater than 70%. This is mainly because nickel has good bonding properties with both titanium and tin, which helps to improve the bonding performance between the first and second metal coatings and the substrate. The addition of cobalt and copper alloy components to the nickel coating improves the corrosion resistance of the metal layer, so as to achieve the purpose of protecting the substrate metal together with the intermediate layer.

[0014] In a preferred embodiment, the thickness of the first metal coating is 1-30 μm, preferably 3-15 μm. The inventors have found that controlling the thickness of the first metal coating within the above range results in the best anode performance. If the thickness of the first metal coating is too thin, it is difficult to achieve the above-mentioned purpose of improving the bonding performance between each metal layer and the substrate, as well as protecting the substrate metal; if the first alloy coating is too thick, it is prone to cracking, and even the coating may brittlely peel off from the substrate.

[0015] In a preferred embodiment, the metal in the second metal plating layer is selected from at least one of tin, antimony, bismuth, nickel, and cobalt, and contains tin, wherein the mass fraction of tin in the second metal plating layer is 80-100%, preferably 90-98%.

[0016] In this invention, the tin content in the second metal coating is greater than 80%, mainly to enable the second metal coating to be fully oxidized and transformed into SnO2 with semiconductor properties. The oxide doping components of metals such as antimony, bismuth, nickel, and cobalt are transformed into SnO2 after oxidation, thereby increasing the carrier content in SnO2 and improving its electronic conductivity.

[0017] In a preferred embodiment, the thickness of the second metal coating is 10-100 μm, more preferably 10-60 μm, and even more preferably 10-20 μm.

[0018] In this invention, the anode performance is optimal when the thickness of the second metal coating is controlled within the above-mentioned range. If the second metal coating is too thin, it cannot meet the purpose of protecting the first coating metal and the base metal after oxidation. If it is too thick, it will form an excessively thick intermediate oxide semiconductor layer after oxidation, which will affect the overall electronic conductivity of the electrode.

[0019] In a preferred embodiment, the oxidant in the acidified oxidant solution is selected from at least one of potassium permanganate solution, potassium dichromate solution, and sodium persulfate, and the acid is selected from at least one of sulfuric acid, hydrochloric acid, and nitric acid.

[0020] Further preferably, the concentration of the oxidant in the acidified oxidant solution is 0.02–0.5 mol / L, preferably 0.05–0.2 mol / L, H + The concentration is 10 -5 ~1 mol / L, preferably 10 -5 ~0.1mol / L.

[0021] In a preferred embodiment, electrode B is immersed in an acidified oxidant solution for ≥20 hours.

[0022] The inventors discovered that immersing electrode B in an acidified oxidant solution for more than 20 hours can fully convert the second metal coating into a metal oxide.

[0023] In a preferred embodiment, electrode C is placed in a manganese-containing solution to grow a manganese dioxide layer through cathodic reduction or anodic oxidation.

[0024] In a preferred embodiment, a manganese nitrate solution is uniformly coated onto the surface of electrode C to obtain a manganese nitrate coating. Then, the manganese nitrate coating is heat-treated at 300-600℃, preferably 300-400℃, to convert the manganese nitrate coating into a manganese dioxide layer. This coating-heat treatment process is repeated 10-20 times to obtain a titanium-based inert anode.

[0025] In a further preferred embodiment, the manganese nitrate solution contains 30% to 50% manganese nitrate by mass.

[0026] Beneficial effects

[0027] This invention proposes a method for preparing a titanium-based inert anode, which mainly involves electrodepositing two metal coatings on a titanium substrate, oxidizing the second metal coating in situ to serve as the intermediate layer of the inert anode, and finally coating an active manganese dioxide layer on the electrode surface with the intermediate oxide layer to obtain a titanium-based inert anode with good electronic conductivity and electrocatalytic activity, and good bonding between the functional layer, the intermediate layer and the metal substrate.

[0028] Compared with existing preparation processes, the technical concept and process principle of this invention have significant characteristics and technical advantages, specifically manifested in:

[0029] (1) The present invention proposes to first electroplate two metal / alloy layers on the surface of a titanium substrate by electrodeposition. The first metal layer has good corrosion resistance and can match the expansion and contraction performance between the second metal layer and the titanium substrate during use when the metal layer is converted into an oxide. This ensures a strong bond between the intermediate oxide layer and the metal substrate and prevents the titanium substrate from being corroded or passivated when the outer oxide layer is damaged.

[0030] (2) The present invention obtains an intermediate oxide layer of an inert electrode by obtaining a second metal coating through in-situ oxidation electrodeposition. This can ensure that the intermediate layer and the first metal coating have a tight bonding performance, and at the same time, the composition of the second metal layer can be adjusted so that the intermediate oxide obtained after oxidation is a doped oxide, thereby increasing the concentration of charge carriers in the oxide semiconductor and thus improving its electronic conductivity.

[0031] (3) The intermediate oxide layer of the titanium-based inert anode prepared by the method of the present invention can avoid the repeated solution / sol brushing-thermal decomposition process, making the preparation process simple and conducive to reducing energy consumption. Attached Figure Description

[0032] Figure 1 The linear voltammetric scan curve of the titanium-based inert anode prepared using Example 1 of the present invention is shown. The oxygen evolution potential of the electrode material can be calculated based on this curve.

[0033] Figure 2 The image shows the constant current polarization curve of the titanium-based inert anode prepared using Example 1 of this invention. The accelerated lifetime of the electrode material can be obtained from this curve. Detailed Implementation

[0034] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0035] Unless otherwise specified, all reagents and raw materials used in this invention are commercially available products or products that can be prepared by known methods.

[0036] The specific embodiments of the present invention are as follows:

[0037] Example 1

[0038] Titanium sheets were cut into 10×50mm shapes to serve as electrode substrates, and the surface oxide layer was removed by grinding. The sheets were then washed sequentially with sodium hydroxide and anhydrous ethanol, followed by drying. The treated titanium sheets were then boiled in a 0.1mol / L oxalic acid solution for 1 hour to etch a textured surface.

[0039] A 10×10mm working area is left on the surface of the treated titanium sheet, and the remaining parts are insulated. Using the titanium sheet as the cathode and a platinum electrode as the anode, a Ni-containing... 2+ 0.5 mol / L, Co 2+ Electrodeposition was carried out in a 0.08 mol / L sulfate plating solution with a cathode current density of 5 mA / cm². 2 After deposition for 15 minutes, the electrode was removed and cleaned to obtain an electrode with the first metal / alloy coating. Electrodeposition was then performed again using a plating solution containing 0.3 mol / L SnSO4 and 0.02 mol / L BiCl3 as the electrolyte, with a cathode current density of 5 mA / cm². 2 The deposition time was 10 minutes, resulting in an electrode with a second metal / alloy coating. The alloy layers were analyzed using SEM and EDS. The thickness of the first metal / alloy coating was 3.8 micrometers, with nickel and cobalt comprising 88% and 12% by mass, respectively. The thickness of the second metal / alloy coating was 10.4 micrometers, with tin and bismuth comprising 94% and 6% by mass, respectively.

[0040] The electrodes were immersed in a 0.05 mol / L potassium permanganate solution (containing 0.05 mol / L sulfuric acid) for 20 hours, then removed, cleaned, and dried.

[0041] A 50% manganese nitrate solution was uniformly coated on the surface of the electrode and heat-treated at 300°C for 30 minutes. This process was repeated 10 times to obtain an electrode with a tin dioxide intermediate layer and a manganese dioxide surface layer.

[0042] Using 1 mol / L Na₂SO₄ and 0.25 mol / L H₂SO₄ as the electrolyte, a titanium-based manganese dioxide inert electrode was prepared as the working electrode, a titanium mesh as the counter electrode, and a mercury / mercurous sulfate electrode as the reference electrode, forming a three-electrode system. Linear voltammetry was performed with a potential range of 0.6–1.4 V and a scan rate of 2 mV / s. The results are as follows: Figure 1 As shown in the figure. Based on this curve, the oxygen evolution current is calculated to be 10 mA / cm². 2 The oxygen evolution overpotential of the electrode is 483mV.

[0043] Using 0.5 mol / L H₂SO₄ as the electrolyte, a titanium-based inert anode was prepared as the working electrode, and a titanium mesh was used as the counter electrode, forming a two-electrode system. Constant current polarization-enhanced lifetime testing was conducted at a current density of 250 mA / cm². 2 The obtained constant current polarization curve is as follows Figure 2 As shown in the figure. Based on this curve, the accelerated lifetime of the electrode is 76.3 hours.

[0044] Example 2

[0045] The operation procedure is the same as in Example 1, except that maleic acid is used instead of oxalic acid, the acid concentration is 0.5 mol / L, and Cu is used. 2+ Replace Co 2+ Cu 2+ The concentration was 0.05 mol / L, with SbCl3 replacing BiCl3, and the SbCl3 concentration was 0.01 mol / L. The electrodeposition time for the first metal / alloy coating was 55 minutes, and the electrodeposition time for the second metal / alloy coating was 20 minutes. Sodium persulfate was used instead of potassium permanganate, and the sodium persulfate concentration was 0.2 mol / L (containing 0.025 mol / L sulfuric acid). The thickness of the first metal / alloy coating was measured to be 14.3 μm, with nickel and copper mass percentages of 81% and 19%, respectively. The thickness of the second metal / alloy coating was 20.5 μm, with tin and antimony mass percentages of 98% and 2%, respectively. The oxygen evolution overpotential of the titanium-based inert anode was 598 mV, and the accelerated lifetime was 80.4 h.

[0046] Example 3

[0047] The operation procedure is the same as in Example 1, except that dimethyloxaloacetic acid is used instead of oxalic acid, and the acid concentration is 0.3 mol / L. 2+The concentration of the anode was 0.1 mol / L. CoCl2 was used instead of BiCl3, and the concentration of CoCl2 was 0.04 mol / L. The electrodeposition time for the first metal / alloy coating was 30 minutes, and the electrodeposition time for the second metal / alloy coating was 15 minutes. Potassium dichromate was used instead of potassium permanganate, and the concentration of potassium dichromate was 0.1 mol / L (the pH was adjusted to 5 with sulfuric acid). The thickness of the first metal / alloy coating was measured to be 9.2 μm, with nickel and cobalt mass percentages of 86% and 14%, respectively. The thickness of the second metal / alloy coating was 16.3 μm, with tin and cobalt mass percentages of 91% and 9%, respectively. The oxygen evolution overpotential of the titanium-based inert anode was 510 mV, and the accelerated life was 76.8 h.

[0048] Example 4

[0049] The operation process is the same as in Example 1, except that NiCl2 is used instead of BiCl3 and the concentration of NiCl2 is 0.02 mol / L. The electrodeposition time for the first metal / alloy coating is 20 minutes, and the electrodeposition time for the second metal / alloy coating is 12 minutes. The electrode with the intermediate oxide layer is used as the working electrode, and the platinum sheet electrode is used as the counter electrode. A surface manganese dioxide active layer is obtained by cathodic electrodeposition in a 0.1 mol / L potassium permanganate solution at a current density of 5 mA / cm². 2 The deposition time was 10 minutes. The thickness of the first metal / alloy coating was measured to be 4.3 micrometers, with nickel and cobalt having a mass percentage of 88% and 12%, respectively; the thickness of the second metal / alloy coating was 11.8 micrometers, with tin and nickel having a mass percentage of 95% and 5%, respectively; the oxygen evolution overpotential of the titanium-based inert anode was 588 mV, and the accelerated lifetime was 77.1 h.

[0050] Comparative Example 1

[0051] Titanium sheets were cut into 10×50mm shapes to serve as electrode substrates, and the surface oxide layer was removed by grinding. The sheets were then washed sequentially with sodium hydroxide and anhydrous ethanol, followed by drying. The treated titanium sheets were then boiled in a 0.1mol / L oxalic acid solution for 1 hour to etch a textured surface.

[0052] A mixed solution of citric acid, ethylene glycol, and tin tetrachloride in a mass ratio of 1:5:0.5 was prepared. The prepared solution was uniformly coated onto the titanium sheet and dried at 75 degrees Celsius. Then, it was decomposed at 450 degrees Celsius for 10 minutes. The above operation was repeated 10 times, with the last decomposition time being 1 hour. A tin dioxide intermediate layer was obtained on the titanium substrate. The thickness of the intermediate layer was measured to be 31.8 micrometers by SEM.

[0053] A 50% manganese nitrate solution was uniformly coated onto the intermediate layer of the aforementioned titanium substrate, and then heat-treated at 300°C for 30 min, repeated 10 times, to obtain an electrode with a tin dioxide intermediate layer and a manganese dioxide surface layer. Linear voltammetry and accelerated lifetime testing were performed on this electrode using the testing method of Example 1. The oxygen evolution overpotential of this titanium-based inert anode was measured to be 667 mV, and the accelerated lifetime was 38.5 h.

[0054] Comparative Example 2

[0055] The operation process is the same as in Example 1, except that the electrodeposition time for the second metal coating is 5 minutes, and the thickness of the second metal / alloy coating is measured to be 4.8 micrometers, in which the mass percentages of tin and bismuth are 92% and 8%, respectively; the oxygen evolution overpotential of the titanium-based inert anode is 558mV, and the accelerated lifetime is 42.1h.

[0056] Comparative Example 3

[0057] The operation process is the same as in Example 1, except that the electrodeposition time for the second metal coating is 60 minutes, and the thickness of the second metal coating is measured to be 62.4 micrometers, of which the mass percentages of tin and bismuth are 93% and 7%, respectively; the oxygen evolution overpotential of the titanium-based inert anode is 687mV, and the accelerated lifetime is 80.1h.

[0058] Comparative Example 4

[0059] The operation process is the same as in Example 1, except that the electrodeposition time for the first metal coating is 5 minutes, the thickness of the first metal coating is measured to be about 2 micrometers, and some surfaces have a discontinuous porous morphology; the oxygen evolution overpotential of the titanium-based inert anode is 558mV, and the accelerated lifetime is 32.4h.

Claims

1. A method for preparing a titanium-based inert anode, characterized in that: Electrode A containing the first metal coating is obtained by first electrodeposition on the surface of a titanium substrate. Then, electrode B containing the bimetallic coating is obtained by second electrodeposition on the surface of electrode A. Electrode B is immersed in an acidified oxidant solution and reacted to obtain electrode C with a metal oxide layer. Then, a manganese dioxide layer is set on the surface of electrode C to obtain a titanium-based inert anode. The metal in the first metal coating is selected from at least one of nickel, cobalt, and copper, and includes nickel, wherein the mass fraction of nickel in the first metal coating is 70-100%. The thickness of the first metal coating is 3-15 μm; The metal in the second metal coating is selected from at least one of tin, antimony, bismuth, nickel, and cobalt, and contains tin, wherein the mass fraction of tin in the second metal coating is 80-100%. The thickness of the second metal coating is 10-60 μm.

2. The method for preparing a titanium-based inert anode according to claim 1, characterized in that: The titanium matrix is ​​first subjected to surface acid treatment in an acid solution; The acid solution is one or more of the following: dihydroxytartaric acid, maleic acid, dimethyloxaloacetic acid, dihydroxymaleic acid, oxalic acid, dichloroacetic acid, dinitrobenzoic acid, 2-ethylmalonic acid, and 2,6-dihydroxybenzoic acid; in the acid solution, H... + The concentration is 0.1~1 mol / L.

3. The method for preparing a titanium-based inert anode according to claim 1, characterized in that: In the acidified oxidizing agent solution, the oxidizing agent is selected from at least one of potassium permanganate solution, potassium dichromate solution, and sodium persulfate, and the acid is selected from at least one of sulfuric acid, hydrochloric acid, and nitric acid. The concentration of the oxidant in the acidified oxidant solution is 0.02~0.5 mol / L.

4. The method for preparing a titanium-based inert anode according to claim 1, characterized in that: Electrode B was immersed in an acidified oxidant solution for ≥20 hours.

5. The method for preparing a titanium-based inert anode according to claim 1, characterized in that: Electrode C is placed in a manganese-containing solution to grow a manganese dioxide layer through cathodic reduction or anodic oxidation.

6. The method for preparing a titanium-based inert anode according to claim 1, characterized in that: Manganese nitrate solution is uniformly coated onto the surface of electrode C to obtain a manganese nitrate coating. Then, heat treatment is performed at 300-600℃ to convert the manganese nitrate coating into a manganese dioxide layer. The coating-heat treatment is repeated 10-20 times to obtain a titanium-based inert anode. The manganese nitrate solution contains 30% to 50% manganese nitrate by mass.